1999
DOI: 10.1002/jccs.199900006
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomy of Triterpenoid Pattern of HPLC of Ganoderma lucidum and Ganoderma tsugae

Abstract: Three strains of Ganoderma tsugae (CCRC36065, CCRC37034, CCRC37038) and three strains of Ganoderma lucidum (CCRC36021, CCRC37029, CCRC37033) were cultivated. Their triterpenoid patterns of the fruit body were analyzed by reverse phase HPLC using a gradient elution of acetonitrile/2% acetic acid (1/4 and 1/2). The triterpenoid patterns of G. tsugae and G. lucidum are different. But similar 2 and 3 dimensional patterns are obtained among three strains of G. tsugae. Different patterns are found among different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The G. lucidum strain (YK-02), which was preserved in Mycelium Center of Biotechnology R & D Institute (Shnang Hor Group, Tainan Hsien, Taiwan), was grown to fruiting body according to the report of Chen et al [10]. It has been identified by Dr. Shen-Hwa Wu (National Museum of Natural Science, Taiwan), using morphology characterization and DNA profiles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G. lucidum strain (YK-02), which was preserved in Mycelium Center of Biotechnology R & D Institute (Shnang Hor Group, Tainan Hsien, Taiwan), was grown to fruiting body according to the report of Chen et al [10]. It has been identified by Dr. Shen-Hwa Wu (National Museum of Natural Science, Taiwan), using morphology characterization and DNA profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Crude triterpenoids of G. lucidum (YK-02) were separated according to the method of Chen et al [10]. Briefly, G. lucidum (YK-02) powder was extracted with 50% ethanol for 1 h. The mixture was filtered, and the filtrate was evaporated to dryness with a rotary evaporator.…”
Section: Preparation Of Crude Triterpenoids From G Lucidum (Yk-02)mentioning
confidence: 99%
“…In a study reported in 1999, Chen et al (1999) were able to use an analysis of triterpenoids to differentiate between G. tsugae and G. lucidum. However, although the three G. tsugae strains tested presented with similar spectral profiles, the three G. lucidum strains tested had profiles that were both very different from those generated from G. tsugae strains, and from each other.…”
Section: Taxonomymentioning
confidence: 99%
“…Triterpenoid content was analyzed (Chang et al, 2006;Chen et al, 1999); 10 g of freeze-dried mycelia was immersed in 150 mL ethanol and incubated in a 65 8C water bath for 1 h. The hot solvent extract was filtered with Whatman No. 5 filter paper to collect the solvent.…”
Section: Analysis Of Triterpenoidsmentioning
confidence: 99%